Pengaruh model pembelajaran discovery learning berbantuan aplikasi Geogebra terhadap kemampuan pemecahan masalah matematis siswa kelas X SMA - Gultom, Rina Gebryella; Surya, Edy (Papanda Journal of Mathematics and Science Research, 2025)
Mathematics is one of the subjects that students consider difficult and less interesting. This can be due to the lack of variety and learning models as well as the proper integration of learning media. One of the impacts of this is the low mathematical problem-solving ability of students. Therefore, this study was conducted to see whether the discovery learning model assisted by the GeoGebra application has an effect on the ability to solve mathematical problems for students in class X of Prayatna Private High School Medan T.A 2024/2025. The research method used was Quasi Experiment with a pretest-posttest control group design. The research sample determined by random sampling consisted of two classes, the first using discovery learning with the help of GeoGebra and the second using direct learning. Data was collected through instruments in the form of pretest and posttest. A comparative analysis of two independent groups using a t-test found that the discovery learning model assisted by the GeoGebra application had a significant effect on the mathematical problem-solving ability of students. In addition, the average score of the experimental class (83.83) was higher than that of the control class (76.66) and the average N-Gain score of the experimental class (75.70) was higher than that of the control class (54.09), showing that the discovery learning model assisted by the GeoGebra application not only had a significant effect but also improved the mathematical problem-solving skills of students. In addition, there is an increase in students' mathematics learning where students become active in the learning process and easily understand the teaching material